Active electrical distribution network : a smart approach - Khan, Baseem; Guerrero, Josep M.; Padmanaban, Sanjeevkumar; Alhelou, Hassan Haes. (New Jersey : Wiley, 2021)
"In recent years, electricity industry is transformed from regulated to deregulated structure. This transformation introduced efficacy and market competition in the energy industry. Different sectors of the electricity industry are deregulated and developed into separate entities such as GENCO, TRANSCO and DISCOMS. Further, smart grid technologies are going to be implemented in electricity sector at the various parts of the world. These technologies in generation, transmission and distribution sectors will supply the rapidly increasing energy demand. These technologies are changing the modern energy systems very rapidly with increasingly multifaceted features. In the present energy sector, power generation, transmission and distribution is not only the main function of the energy utilities rather system stability, reliability, efficacy and security have becomes the major issues. These issues help energy utilities for managing, controlling and operating the generation sources for the long term basis, with reducing their effects on ecology and environment. Planning and operation of the energy sector requires efficiency for maximizing the advantages for the utilities and consumers, concurrently. Further, energy saving can be terms as the power generation which contributes to the minimization of the carbon emissions in the globe's climate. For solving the above discussed problems, various techniques are continuously emerging. Implementation of these smart grid technologies supports for exploring the renewable energy sources with their optimum utilization. But still there is a huge gap between existing power generation and load demand. To coup up this energy gap utilities are depending on the traditional reliable energy sources along with the intermittent renewable energy sources such as solar, wind, fuel cell etc. Thus, for the reliable operation of the electricity industry traditional sources of energy production are studied in various part of the world. The dependence on these traditional generation sources creates problem for the environment. Thus, utilization of the renewable energy sources and techniques for supplying the demand is important issue for enhancing the energy security. In this regard, green energy sources got the attention from the researchers all over the globe. These sources will enhance the high integration of the renewable energy sources in the utility grid. The main issue with these renewable energy sources is their variable nature of generation depends on environmental conditions. Due to this, energy generation from solar and wind sources are fluctuating in nature and directly affects the generation frequency, voltage and waveform and therefore, affected the quality and amount of supplying energy to the integrated grid system. The energy demand will increase by 70% from the present demand in the year of 2030. But the traditional energy sources are continuing depleting day by day that raise the grave concern of energy usage per capita. The energy consumption per capita described the living standard of any country. Thus more number of renewable energy sources is required to explore, which are locally available with optimization methods for enhancing the energy generation efficiency. The available issues of the Active power distribution system clearly indicate that the available techniques of planning, control and operation required more efficient solutions"--
Includes bibliographical references and index.
Keywords: Electric power distribution